Measuring the neutrino mass hierarchy with KM3NeT/ORCA - Hofestädt, Jannik (Journal of Physics: Conference Series, 2020)
ORCA is the low-energy branch of KM3NeT, the next-generation research infrastructure hosting underwater Cherenkov detectors in the Mediterranean Sea. ORCA's primary goal is the determination of the neutrino mass hierarchy by measuring the matter-induced modifications on the oscillation probabilities of few-GeV atmospheric neutrinos. The technical design of the ORCA detector foresees a dense configuration of optical modules, optimised for the study of interactions of neutrinos in the energy range of 3-30 GeV. The first ORCA detection string was successfully deployed on 22nd September 2017 and is providing high-quality data since then. With an instrumented mass of 8 Mton for the full-size ORCA detector, it will be possible to probe with a high-statistics neutrino sample a wide range of energies and baselines through the Earth. This allows to detmerine the neutrino mass hierarchy with 3 σ after 3-4 years of operation, to probe the unitarity assumption of 3-neutrino mixing with a high-statistics measurement of tau-neutrino appearance in the atmospheric neutrino flux, and to improve the measurement precision on other oscillation parameters.
CRIS-Team Scopus Importer:2020-02-18